Past, present and future of Coal Bed Methane (CBM): a review with special focus on the Indian scenario. Issue 2 (1st February 2023) - Joshi, Dev; Prajapati, Piyush; Sharma, Pushpa; Sharma, Anjali
ABSTRACT: The rapid depletion of conventional hydrocarbons has shifted the industry's focus to other sources of energy which are uncommon. Unconventional opportunities are more important than the conventional opportunities, and they require high capital levels to be achieved. This analysis intends to fill a gap in the market with a modern and concise overview of Coal Bed Methane for students and newcomers to the business. This study discusses the various categories of coal rankings and the different generations of CBM. It covers the background of CBM industry along with its journey throughout these years. Considering India's increasing economic and population growth, innovative approaches to optimize sources of energy is an urgent need. As a result, India has been actively researching and improving its CBM capital through international tendering processes over all these years. CBM is an unconventional natural gas source and is currently being evaluated as a potential option for fulfilling India's increasing energy demands. Therefore, complete analysis of the Indian CBM Market has been conducted discussing various CBM extraction techniques. An evaluation of the impact of India's geography on CBM market has been performed. The study concludes with discussion of the future of CBM in India and throughout the world.